The influence of work environment on training effectiveness: the case of Perpustakaan Negara Malaysia / Nur Ashikin Mohamed Ismail - Mohamed Ismail, Nur Ashikin (2013)
Training is widely understood as communication directed at a defined population for the purpose of developing skills, modifying behavior, and increasing competence. Generally, training focuses exclusively on what need to be known. In contrast to informal training which is embedded in most instances of human exchange, formal training have stated goals, content, and strategies for instruction. In order to identify whether or not a training initiative is effective, depends on how well learner are able to apply what they learned to improve job performance. Furthermore, without a significant and observable return on investment, training is seen as a waste of time and valuable resources. However, whether or not a learner is able to successfully transfer their knowledge to the workplace it is wholly dependent upon the learner. Instead there are many different types of influential factor that effect job training, and in fact, most of them do not depend on the learner. Nurhazani, M.S et all (2012) Perpustakaan Negara Malaysia also always provide training to their employees as a strategies to achieve performance. In Perpustakaan Negara Malaysia it is becoming more essential to manage competent employees as the most valuable resource of organization, because the need for effective and efficient delivery of service to the public by Perpustakaan Negara Malaysia. In private sector, performance evaluation is based on the profit maximization. Means while in public sector, service delivery for the enhancement of the living standard of the people or citizen as a customer are deemed to be the performance achievement in public organization such as Perpustakaan Negara Malaysia. That is why Perpustakaan Negara Malaysia always ensure their employees are being trained enough to serve the public. Perpustakaan Negara Malaysia aims by providing training to reduce gap between public expectation and performance level in Perpustakaan Negara Malaysia. Despite the development that has taken place regarding training program, there is still room for reseach. This study tries to determine the work environment factor that influence the training program effectiveness at Perpustakaan Negara Malaysia an in view the importance of these program. Because the work environment is necessary and one of the key factor to determine the learning in the training program and its crucial in determining the application of skills in the workplace.